2020
DOI: 10.22571/2526-4338282
|View full text |Cite
|
Sign up to set email alerts
|

Honeybees and their products as bioindicators for heavy metal pollution in Malta

Abstract: In this study, honeybees, propolis, air, soil and plant samples were gathered from two contrasting sites Ħal Luqa (industrial area) and L-Imġarr (agricultural area) in mainland Malta. Superficial heavy metals were extracted from the samples and tested using microwave plasma-atomic emission spectrometry in order to determine the concentrations of Ag, As, Cd, Cr, Cu, Pb, Sn, Zn, Ni and Hg. The honeybee and propolis samples were digested using nitric acid and hydrogen peroxide and then ashed using a muffle furnac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In general, the results of previous studies have mainly indicated an increased concentration of heavy metals and arsenic in honey produced near mining areas; however, in most cases, they did not exceed illegal limits [12], and hence, honey is safe for use and human health [66,67]. However, some authors have called for caution [18,63,68,69], which is also the case with the authors of this study.…”
Section: Discussionsupporting
confidence: 55%
“…In general, the results of previous studies have mainly indicated an increased concentration of heavy metals and arsenic in honey produced near mining areas; however, in most cases, they did not exceed illegal limits [12], and hence, honey is safe for use and human health [66,67]. However, some authors have called for caution [18,63,68,69], which is also the case with the authors of this study.…”
Section: Discussionsupporting
confidence: 55%
“…1881/2006 for crustaceans (0.4 µg/g) [32]. Because the drone brood used in our research came from an industrial area, high heavy metal limits could have been the cause behind this factor, similar to [33,34]. This was contrary to another document [35], which identified the drone brood as a toxicologically safe raw material.…”
Section: Determination Of Element Contentmentioning
confidence: 69%
“…Particularly in living matrices, heavy metals may interfere with beneficial metals some of the latter being replaced by heavy metals that would result in the erratic physiological functioning of bodily systems. This is not an issue related only to mammals and humans, but such erratic behavior, in terms of morbidity and mortality has been observed in other animals, such as insects [13], and also in plants. Some of these heavy metals accumulate in biological systems and one source for such accumulation is the daily and/or repeated use of cosmetic products such as face powders, lipsticks and eye shadows [2].…”
Section: Heavy Metalsmentioning
confidence: 98%